Strategic Technology Integration in M and A: From Due Diligence to Value Realization - Amrita Chatterjee, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article presents a comprehensive framework for strategic systems integration during mergers and acquisitions (M&A), focusing on the critical intersection of technology infrastructure harmonization and enterprise value creation. By examining the complexities of post-merger systems integration, it introduces a structured approach that encompasses data platform unification, operational alignment, and value optimization strategies. The framework addresses key challenges in technology stack evaluation, data governance, and integration methodology while providing practical insights for maximizing synergy realization. Through an analysis of successful M&A cases and industry best practices, this article demonstrates how effective systems integration can significantly impact enterprise valuation and operational efficiency. It suggests that a well-orchestrated systems integration strategy, supported by robust data management and clear implementation methodologies, serves as a crucial driver for M&A success and long-term value creation in modern enterprise environments.
Keywords: Systems Integration Strategy; Post-merger Technology Harmonization; Enterprise Value Optimization; Data Platform Unification; M&A Technology Integration